Research on corrugated interface formation mechanism and mechanical properties of the CFR flat Mg/Al clad plate - Sha Li; Zhibing Chu; Hailian Gui; Leifeng Tuo; Jianchao Han; Tao Wang; Qingxue Huang (Journal of Materials Research and Technology, 2023)
Corrugated-flat rolling (CFR) process was employed to manufacture the Mg/Al clad plate at 400 °C. The CFR process can produce flat Mg/Al clad plate with excellent shape and corrugated interface. EBSD analysis and tensile-shear tests were conducted to study the corrugated interface characteristics of the flat plate, revealing its strengthening mechanism. After the second-pass flat rolling process, the interface intermetallic compounds (IMCs) layer formed by heat treatment between passes broke, causing new bonding interface observed in the gap between the fractured IMCs. Intermittently distributed IMCs played a “pinning” role on the Mg/Al interface and restrained each other with the new bonding interface, which can improve the cooperative deformation ability of Mg plate and Al plate, and enhance the interface bonding strength. The interface tensile-shear strength at trough position was 33.97 MPa, which was higher than that at the peak position (24.17 MPa). During the second-pass flat rolling process, strong compressive stress was applied, improving the stress uniformity of the flat plate and refining metal grains, resulting in an improvement in tensile properties. The rolling UTS of flat plate was 255.77 MPa, and the fracture EL was 5.72%.